INFLASI DI ERA GLOBAL DENGAN PENDEKATANPHILLIPS-CURVE - Nawatmi, Sri (Optimum: Jurnal Ekonomi dan Pembangunan, 2016)
This study aims to analyze infl ation in Indonesia by using the New KeynesianPhillips Curve. The study used Vector Autoregressive (VAR) with the type of VECM (Vector Error Correction Model). VECM is one of restrictive VAR. The fi rst step of VAR is determining endogenous and exogeneous variables based on the theory. Estimation results indicate that the Error Correction Term (ECT) is signifi cantly negative (-0.675167). It means that there was the existence of the error term, and the negative sign indicates that an error capable of leading to equilibrium. Based on the results obtained of VECM calculation, expected infl ation had negative effect on inflation in Indonesia (-0.913099). Indonesia output gap had positive effect (62.98311) while world output gap did not affect infl ation in Indonesia. It means that domestic factors more determine infl ation in Indonesia than the foreign factors. Thus, Bank Indonesia as price stabilizer will be easier to create a policy to tackle infl ation because domestic factors are easier to control than the foreign factors.